AN SMS AND USSD MODEL FOR LOCATION-BASED MOBILE ADVERTISING IN MICROENTERPRISES - THIGA, MOSES MWANGI (Kabarak University, 2014)
Technological and financial limitations have hampered the effective advertisement of products and services by microenterprises thus limiting their contribution towards national economic growth. Recent advances in mobile technologies makes the use of location based mobile advertising (LBMA) a viable option in addressing this challenge. However, a majority of LBMA are developed for use on smart and feature phones with inbuilt positioning and program execution capabilities thus leaving out a majority of microenterprises who use basic phones. This study therefore examined the use of alternative positioning methods, namely symbolic and network based geo-location, and device independent system access methods; SMS and USSD, for the development of LBMA for use by microenterprises. Functional decomposition and rapid prototyping methodologies were utilized to develop a suitable LBMA application model and system prototype respectively. The prototype utilizing network based geo-location proved to be successful in delivering LBMA services to microenterprises. The delivery of LBMA services to microenterprises using network based geo-location, SMS and USSD was therefore found to be feasible and practical. It is therefore recommended that this approach be scaled up and commercialized whilst addressing emergent adoption issues such as cost and security concerns occasioned by the use of user’s real time locations
Keywords: SMS; USSD; Location-based mobile advertising; microenterprises